KAZAKH MUSIC CULTURE ON THE GLOBALIZATION CROSSROADS: ETHNIC TRADITIONS VERSUS COMPOSER SCHOOL IN INTERCULTURAL INTERACTION - Raimkulova Aktoty (Scientific Journal of Pedagogy and Economics, 2020)
At the present stage, Kazakh musical culture is heterogeneous. It represents traditions coexisting at the same time and interacting with each other: Kazakh ethnic and newly established composer school (tradition). Examining changes in cultural landscapes of the 20th century I reveal the peculiarities of interaction and dialogue between two kinds of culture: ethnic and global (endogenous and exogenous). The procedures include the complex study of the history of Kazakh culture in the 20th century, stylistic analysis of traditional and composer’s music, semiotic approach to intercultural interaction, as far as a comparative analysis of oral and written music of 19th and 20th centuries. On one hand, dramatic changes in the structure of music culture were caused by external objective reasons: new industrial and postindustrial civilization phases (urbanization and information technologies); intensification of interaction with western (mainly Russian) cultures, etc. On the other hand, some changes were inspired by inner factors: diverse development of local song and kui (dombyra piece) traditions; Soviet cultural policy. As a result new type (or layer) of national culture – Kazakh composers’ music – appeared. It was connected with the formation of a national style based on transcriptions and borrowing. Traditional music was influenced by new social institutions (philharmonic halls, theatres, radio, conservatoire) that caused changes in the creative process (decrease of oral transmission, lack of traditional social context) as well as in the style (virtuoso performance, new genres of songs).